Keanekaragaman tumbuhan survival di bagian selatanBukit tlogodringo tawangmangu karanganyar - Argiyanti, Anna; Suryani, M.Sc., Dra. Titik Suryani, M.Sc (2016)
Indonesia has a very abundant biodiversity one plant diversity. Plant survival is a plant that is safe for consumption by humans. Tlogodringo hill has a peak altitude of 2,054 m. asl in the form of fairly dense forest. The purpose of this study to determine the survival of plant diversity which is in the southern part of Bukit Tlogodringo. Sampling of plants by drawing a line along 5 meters at an altitude of 1,600 m . asl range. and 1,800 m asl. asl and recorded, quantify, and identify plant survival were found. The research found 13 plant species include Alsophila sp., Pityrogramma sp., Triumfetta sp., Centella asiatica, Borreri aalata, Polygala paniculata,Desmodium triflorum, Imperata cyliandrica, Borreria leavis, Eupatorium riparium, Oplismenus burmanii, Euphoria logan, and Eupatorium odoratum. Plant survival that dominates the southern part of Bukit Tlogodringo is Borreria alata with dominance index (C) 21 × 10-2 amounted to 46.15% and the lowest Polygala paniculata with dominance index (C) 48 × 10-7 0.21%. Diversity of plant species is said to be moderately Tlogodringo Hill diversity index (H ') of 1.69